Sampling touch DNA from human skin following skin‐to‐skin contact in mock assault scenarios—A comparison of nine collection methods. Issue 5 (29th April 2021) - Kallupurackal, Venus; Kummer, Sonja; Voegeli, Pamela; Kratzer, Adelgunde; Dørum, Guro; Haas, Cordula; Hess, Sabine
Abstract: Collection of touch DNA from an offender on the victim's skin can provide relevant evidence for investigations of criminal cases. Therefore, the choice of the optimal sample collection method is crucial. In this study, we investigated the recovery of STR profiles from touch DNA on human skin by comparing nine different collection methods: the dry and wet cotton swabs in three different movements, the double‐swab (wet–dry) method, the wet and dry Copan FLOQSwabs™, and the Scene Safe FAST™ minitapes. Mock assault scenarios were conducted with a male offender grasping the forearms of a female victim. Samples were collected from the assaulted area of the victim's skin, and the recovery of the offender's STR profile was evaluated. Our results indicate that the different swabs and swabbing techniques did not have a distinct impact on the STR recovery; however, the lowest STR recovery was achieved with Scene Safe FAST™ minitapes. In addition, we compared the double‐swab method to the single‐swab method by analyzing the DNA quantity of the wet and dry swabs separately. We found on average 13.7% more offender DNA using the double‐swab method, but this did not translate into higher STR recovery. Our findings indicate that several methods perform equally well when collecting touch DNA from human skin, although SceneSafe FAST™ minitapes seem to be the least adequate for this purpose.